Factors associated with the duration of viral shedding in adults with COVID-19 outside of Wuhan, China: a retrospective cohort study. (July 2020) - Qi, Lin; Yang, Yong; Jiang, Dixuan; Tu, Chao; Wan, Lu; Chen, Xiangyu; Li, Zhihong
Highlights: This study focused on the duration of viral shedding and risk factors in patients with COVID-19 outside of Wuhan, China. The median duration of viral shedding in the current study was 17 days. The highest temperature at admission, time from symptoms onset to admission and hospital length of stay were risk factors. Abstract: Objectives: To investigate factors associated with the duration of viral shedding in patients with COVID-19, outside of Wuhan. Methods: In this retrospective cohort study, patients with laboratory-confirmed COVID-19 in Changsha, China were included. Clinical characteristics, laboratory findings, treatment, and outcome were retrieved. Univariate and multivariate analyses were performed to explore potential factors. Results: Overall, 147 patients with COVID-19 were included. The median duration of viral shedding (the number of days from symptoms onset until the successive negative detection of SARS-CoV-2 RNA) was 17 days (interquartile range [IQR], 12–21). Multivariate Logistic regression analysis indicated that the highest temperature at admission (odds ratio [OR], 5.200; 95% confidence interval [CI]: 1.190−22.726; p = 0.028), time from symptom onset to admission (OR, 1.740; 95% CI: 1.296−2.337; p < 0.001) and hospital length of stay (OR, 1.604; 95% CI: 1.262−2.040; p < 0.001) were risk factors for prolonged duration of viral shedding. Conclusions: This study, with a relatively large sample size, focused on the duration of viral shedding and related factors in patients with COVID-19, outside of Wuhan, China. Potential risk factors were identified and should be taken into consideration for the strategy of quarantining infected patients.